ダイ10ジ ナンキョク チイキ カンソクタイ キョクコウ チジキ ブモン ガイホウ オモニ VLF エミッション オ チュウシン トシテ - 林, 幹治; ハヤシ, カンジ; HAYASHI, Kanji (国立極地研究所, 1971)
P(論文) This is a preliminary report of the sections of aurora and geomagnetism of the wintering party of the 10th Japanese Antarctic Research Expedition in 1969-1970. Among various observations carried out in these sections, VLF emission phenomena are described especially. The report deals with detailed dynamic spectra of polar chorus at the time of ssc's and si's and frequency variations of polar chorus in these events. Close relationship between low latitude magnetic micropulsations, pc-2 and pc-3, and modulated patterns of polar chorus dynamic spectrum is also shown. Early morning VLF emission phenomenon "auroral chorus" is defined in relation to magnetic micropulsations, pulsating aurorae, and negative geomagnetic bay events. departmental bulletin paper